Can Digital Transformation Improve ESG Performance? -- Empirical Evidence from A-share Listed Companies - Du, Lingyun (Transactions on Economics, Business and Management Research, 2024)
Taking the A-share listed companies on Shanghai and Shenzhen stock exchanges from 2009 to 2020 as samples. This paper uses Python to construct an index of digital transformation by analyzing text data from enterprises’ annual reports and examines its impact on enterprise ESG performance and impact channels. The empirical results show that digital transformation can significantly improve the ESG performance of the enterprise. This finding is still valid after a series of robustness and endogeneity tests. Mechanistic tests show that digital transformation contributes to ESG performance by enhancing the capability for green innovation and improving the quality of information disclosure. Heterogeneity analysis shows that the effectiveness of digital transformation is affected by the nature of property rights and the management’s green perception. This research expands the application of enterprise digital transformation and provides solutions for enterprises to achieve sustainable development.